Detained Persons Incarcerated for the First Time and Needing Acute Psychiatric Care: Sociodemographic and Clinical Characteristics - D'Orta, Isabella; Guilbert, Nicolas; Pierrard, Mathieu; Herrmann, François R.; Giannakopoulos, Panteleimon (Frontiers in Psychiatry, 2022)
Among detained persons, those incarcerated for the first time (FTI: first time incarceration) are known to present long-standing psychological vulnerability but also suffer significant deterioration of their mental health during the first year following imprisonment. Whether the patterns of psychiatric morbidity differ in FTI cases compared to cases with repeated and long term incarceration (RLTI) is still a matter of debate. We examined the sociodemographic and clinical differences between a subgroup of FTI vs. one of RLTI in a series of 139 randomly selected detained persons admitted to an acute psychiatric ward located in the central prison of Geneva, Switzerland. Fisher exact, unpaired Student t and Mann-Whitney U tests were used to explore sociodemographic (age, gender, marital status, religion, knowledge of French, education) and clinical (psychiatric outpatient care, suicidal behavior, psychiatric diagnosis) differences between the two groups. Subsequently, univariate and multiple logistic regression models were used to detect the variables associated with FTI. The proportion of women was significantly higher in the FTI compared to the RLTI group. FTI cases were also more frequently separated or divorced, with less frequent religious affiliation. 16.9% of FTI cases but only 1.3% of RLTI cases had a clinical diagnosis of depression. In multiple regression models, female sex and lower religious affiliation rate were associated with FTI status. Among diagnostic categories, depression was strongly related to FTI status both in univariate and multivariable models. Importantly, this was not the case for adjustment disorders, previous history of psychiatric care and suicidal behavior. Our observations support the assumption that FTI cases with lower affective support, less religious investment and without psychiatric care prior to imprisonment are particularly vulnerable to depressive illness.